Repeat-based holocentromeres influence genome architecture and karyotype evolution - Hofstatter, Paulo G; Thangavel, Gokilavani; Lux, Thomas; Neumann, Pavel; Vondrak, Tihana; Novak, Petr; Zhang, Meng; Costa, Lucas; Castellani, Marco; Scott, Alison; Toegelová, Helena; Fuchs, Joerg; et al. (Cell, 2022)
The centromere represents a single region in most eukaryotic chromosomes. However, several plant and animal lineages assemble holocentromeres along the entire chromosome length. Here, we compare genome organization and evolution as a function of centromere type by assembling chromosome-scale holocentric genomes with repeat-based holocentromeres from three beak-sedge (Rhynchospora pubera, R. breviuscula, and R. tenuis) and their closest monocentric relative, Juncus effusus. We demonstrate that transition to holocentricity affected 3D genome architecture by redefining genomic compartments, while distributing centromere function to thousands of repeat-based centromere units genome-wide. We uncover a complex genome organization in R. pubera that hides its unexpected octoploidy and describe a marked reduction in chromosome number for R. tenuis, which has only two chromosomes. We show that chromosome fusions, facilitated by repeat-based holocentromeres, promoted karyotype evolution and diploidization. Our study thus sheds light on several important aspects of genome architecture and evolution influenced by centromere organization.
Keywords: holocentric chromosomes; Plants; dysploidy; centromera; whole-genome duplication; Centromere; spatial genome organization; transposable elements; Rhynchospora; centromere; karyotyp; molekulární evoluce; Evolution, Molecular; rostliny; Cyperaceae; genome regulation; Animals; zvířata; šáchorovité; Karyotype